A highly efficient FeP/CeO2–NF hybrid electrode for the oxygen evolution reaction. Issue 30 (17th March 2020) - Liu, Jian; Gao, Yan; Wei, Yu; Chen, Xuyang; Hao, Shengjie; Ding, Xin; Pan, Lijun
Abstract : A FeP/CeO2 –NF hybrid electrode was synthesized by a simple electrodeposition and high-temperature phosphorization method. The electrode exhibits high performance toward the OER, which outperforms most reported transition metal phosphide materials. Abstract : Transition metal phosphides have been proven as highly efficient electrocatalysts. In this study, a FeP/CeO2 –NF hybrid electrode was prepared by a simple electrodeposition and high-temperature phosphorization method. The electrode exhibits outstanding performance for the OER with an overpotential of only 245 mV at a current density of 100 mA cm −2, a Tafel slope as low as 39.1 mV dec −1 and an excellent durability for 50 h at a current density of 10 mA cm −2 in an alkaline solution. Such significant high performances are attributed to a combined effect of the excellent electron conductivity of CeO2 and unique uneven columnar structure of the electrode.